2021
DOI: 10.1108/ijppm-05-2020-0231
|View full text |Cite
|
Sign up to set email alerts
|

Talent management in government organizations: identification of challenges and ranking the solutions to address them

Abstract: PurposeThe main aim of this research is to rank and prioritize the solutions to address the challenges for the successful implementation of talent management (TM) in government banks in Iran.Design/methodology/approachThis paper has identified the challenges of TM implementation in government banks and proposed the solutions to address these challenges through a review of the extant literature. The identified challenges and solutions were ranked using two multi-criteria decision-making (MCDM) methods called PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
(92 reference statements)
0
3
0
5
Order By: Relevance
“…Menurut (Sehatpour et al, 2021) setidaknya ada empat faktor yang akan dihadapi dalam implementasi manajemen talenta di sektor publik, yaitu budaya, manajerial, sumber daya manusia, dan lingkungan. Penjelasannya sebagai berikut: 1.…”
Section: Faktor Yang Memengaruhi Manajemen Talenta Sektor Publikunclassified
See 3 more Smart Citations
“…Menurut (Sehatpour et al, 2021) setidaknya ada empat faktor yang akan dihadapi dalam implementasi manajemen talenta di sektor publik, yaitu budaya, manajerial, sumber daya manusia, dan lingkungan. Penjelasannya sebagai berikut: 1.…”
Section: Faktor Yang Memengaruhi Manajemen Talenta Sektor Publikunclassified
“…Sementara itu, studi yang dilakukan oleh Sehatpour et al (2021) yang meneliti tantangan dan solusi dalam menjawab tantangan penerapan manajemen talenta di sektor publik menghasilkan temuan yang menarik. Menurut Sehatpour et al (2021) setidaknya ada empat tantangan dari empat faktor yang akan dihadapi dalam implementasi manajemen talenta di sektor publik, yaitu budaya, manajerial, sumber daya manusia, dan lingkungan. Penjelasannya sebagai berikut: 1.…”
Section: Tantangan Manajemen Talenta Sektor Publikunclassified
See 2 more Smart Citations
“…Further, the use of MCDM in other HR areas is scant. Sehatpour et al (2021) is one the primary study that identified the challenges of talent management in Iran. The identified impediments and solutions were ranked using two MCDM methods called PROMETHEE and VIKOR.…”
Section: Literature Reviewmentioning
confidence: 99%